(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2019)
Researchers and Practitioners advocated that modularity aspect of software is highly desirable and significant for developing quality oriented maintainable software. Despite the fact modularity is vital and highly significant aspect for software development process, it is poorly managed. This paper here highlights the importance of modularity broadly and also as an important contributor of software maintainability. In this paper a correlation between the major attributes of object oriented design and modularity has been ascertained. A modularity quantification model using multiple linear regression has been proposed for object oriented design. Finally, the validation of the proposed modularity quantification model is made known by means of experimental tests and the results show that the model is highly significant.